British Women Travellers in the Long Nineteenth Century
XX, 411 p. 16 illus., 14 illus. in color.
Keywords: During the long nineteenth century, British women reframed the masculine paradigm of the Grand Tour. They created a feminist travel gaze, intentionally or unintentionally, that differed from that of male peers. Unlike their brothers, who went for personal edification, women with means left their English homes for the great Italian cities of Florence, Naples, and Rome to escape personal disappointments and the social limitations imposed by parents, spouses, and society. The anonymity of travel to a distant land and new freedoms fostered political and creative achievements, including entrepreneurial journalism, literary masterpieces, and social advocacy for their gender, which redefined the contours of the Anglo-Italian cultural landscape. The historical evidence presented here testifies to the life-changing capacity of travel and firmly demonstrates how British women’s history and literature enriches and broadens narratives about Britain and the World. Marilyn D. Button is a Professor of English at Lincoln University of Pennsylvania in the USA. She is co-editor of two books: The Foreign Woman in British Literature: Exotics, Aliens, and Outsiders (1999) and The Victorian Case for Charity: Essays on Responses to English Poverty by the State, the Church and the Literati (2013). Jessica A. Sheetz-Nguyen is an Emerita Professor of History at the University of Central Oklahoma and an Adjunct Professor of History at the University of Maryland Global Campus in the USA. She is the author of Victorian Women: Unwed Mothers and the London Foundling Hospital (2012) and co-editor of The Victorian Case for Charity: Essays on Responses to English Poverty by the State, the Church, and the Literati (2013). .